Bioinformatics managing scientific data - Lacroix, Zoe.; Critchlow, Terence (San Francisco, CA : Morgan Kaufmann Publishers, 2003)
Life science data integration and interoperability is one of the most challenging problems facing bioinformatics today. In the current age of the life sciences, investigators have to interpret many types of information from a variety of sources: lab instruments, public databases, gene expression profiles, raw sequence traces, single nucleotide polymorphisms, chemical screening data, proteomic data, putative metabolic pathway models, and many others. Unfortunately, scientists are not currently able to easily identify and access this information because of the variety of semantics, interfaces, a.
Front Cover; Bioinformatics: Managing Scientific Data; Copyright Page; Contents; Preface; Chapter 1. Introduction; Chapter 2. Challenges Faced in the Integration of Biological Information; Chapter 3. A Practitioner's Guide to Data Management and Data Integration in Bioinformatics; Chapter 4. Issues to Address While Designing a Biological Information System; Chapter 5. SRS: An Integration Platform for Databanks and Analysis Tools in Bioinformatics; Chapter 6. The Kleisli Query System as a Backbone for Bioinformatics Data Integration and Analysis
Includes bibliographical references and index.
Keywords: Bioinformatics; Computational Biology -- Methods; Information systems; Systems Integration; Integrated Advanced Information Management Systems; Electronic books